Hukum Islam dan Hukum Positif: Perbedaan, Hubungan, dan Pandangan Ulama - Yudha, Alda Kartika (Faculty of Law, University of Ahmad Dahlan, 2017)
Since 3 May 1924 when Islamic khilafah fell out, there are so many people with their movements who want to declare and dream the resurrection of khilafah state with Islamic law being used propely. Some of them begin with promoting sharia law to be positive law in Islamic country, and this topic has became interesting theme to be discussed ever since. Ever since, the debate among Muslims whether it is must or not to promote sharia law becomes positive law began. Â One think that the side who wanât to aplly sharia law as positive law is kafir and fasiq (this is according to al-Maidah 44, 45 and 47). The others state that itâs not has to be like that with their reasonable arguments. In our opinion, since this is still in domain of ijtihadi, the differences among them is natural to be happened.